Predictors of successful vaginal delivery following cesarean section - Rondón-Tapía, Martha (2023)
Objective: To determine predictors of successful vaginal delivery following primarytransverse segmental cesarean section for non-recurring cause. Design. Casecontrolstudy. Institution: Hospital Central "Dr. Urquinaona", Maracaibo, Venezuela.Methods: Pregnant women with spontaneous onset of labor and history ofcesarean section with transverse incision in the lower segment for non-recurrentcause. The trial of labor was considered successful if it ended in vaginal delivery.Main study measures: Maternal age, parity, frequency of labor prior to previouscesarean section, gestational age at delivery, station of fetal cephalic presentation atadmission, and fetal weight. Results: A total of 126 pregnant women were selected,of whom 85 (67.4%) had successful trials (vaginal delivery), while 41 (32.5%) had afailed trial. No differences in general characteristics were found between groups (p= ns). Univariate analysis showed that fetal weight equal to or less than 3,500 grams,station of fixed or engaged fetal cephalic presentation, and gestational age less than40 weeks were significant predictors of successful trial of labor outcome (p < 0.05).Logistic regression analysis showed that fetal weight equal to or greater than 3,500grams (p = 0.04) and station of floating - insinuated fetal cephalic presentation (p =0.03) retained significance as predictors. Conclusion: Predictors for a successful trialof vaginal delivery following cesarean section were fetal weight less than or equal to3,500 grams and station of fixed or engaged fetal cephalic presentation.